OKSIGEN TERLARUT DAN pH DI AIR SISIPAN SEDIMEN MANGROVE DAN PESISIR DI DESA BULUTUI KECAMATAN LIKUPANG BARAT - Mikhael P. Pinontoan; James J.H. Paulus; Stenly Wullur; Rizald M. Rompas; Elvy Like Ginting; Wilmy E. Pelle (JURNAL PESISIR DAN LAUT TROPIS, 2023)
This research was conducted in Bulutui Village, West Likupang District, related to theproblems raised how is the solubility of Dissolved Oxygen (DO) and the pH of sediment-insertedwater at mangrove locations, and on the coast, then this research aims to find out how the solubility ofoxygen (DO), and acidity (pH) of sediment-inserted water in mangrove ecosystems and on the coastin Bulutui Village, West Likupang District. Based on the results of measurements that have beencarried out in Bulutui Village, West Likupang District, it was found that the value of the dissolvedoxygen content at the mangrove location was in the range of 0.36 – 1.98 ppm, with an average of0.98 ppm, the pH value ranged from 6.16 – 6.89 with an average value of 6.04. In coastal locations,the dissolved oxygen content ranges from 1.26 to 2.87 ppm, with an average of 2.09 ppm, the pHvalue ranges from 6.78 to 8.90, with an average value of 8.34. The statistical t test showed that therewas a difference between the dissolved oxygen values in the sedimentary water in the mangrovesand the coast, as well as the acidity (pH). Keywords: sediment; Inset Water, Dissolved Oxygen, pH Acidity ABSTRAK Penelitian ini dilakukan di Desa Bulutui Kecamatan Likupang Barat, berkaitan denganpermasalahan yang dikemukakan bagaimanakah kelarutan Oksigen Terlarut (DO) dan pH air sisipansedimen pada lokasi mangrove, dan di Pesisir pantai, selanjutnya penelitian ini bertujuan untukmengetahui bagaimana kelarutan oksigen (DO), dan keasaman (pH) air sisipan sedimen padaekosistem mangrove dan di pesisir di Desa Bulutui Kecamatan Likupang Barat. Berdasarkan hasilpengukuran yang telah dilakukan di Desa Bulutui Kecamatan Likupang Barat ditemukan nilai darikandungan oksigen terlarut pada lokasi mangrove adalah berkisar 0,36 – 1,98 ppm, dengan rataratanya 0,98 ppm, nilai pH berkisar 6,16 – 6,89 dengan nilai rata rata 6,04. Pada Lokasi pesisirdengan kandungan oksigen terlarut berkisar 1,26 – 2,87 ppm, dengan rata rata 2,09 ppm nilai pHberkisar 6,78 – 8,90, dengan nilai rata – rata 8,34. Uji statistika t test menunjukkan adanyaperbedaan antara nilai oksigen terlarut pada air sisipan sedimen di mangrove, dan pesisir, demikianjuga keasaman (pH). Kata Kunci: Sedimen; Air sisipan, Oksigen Terlarut, Keasaman pH